Comparative paleogenomics of crucifers: ancestral genomic blocks revisited. (April 2016) - Lysak, Martin A; Mandáková, Terezie; Schranz, M Eric
Highlights: We revisit the concept of the Ancestral Crucifer Karyotype (ACK) and the definition of a revised set of 22 conserved genomic blocks across the Brassicaceae family including Arabidopsis and crop Brassicas. We review how the ACK has been utilized for the analysis of a remarkable thirty-five crucifer genomes to date. We discuss mechanisms of genome reorganization leading to block shuffling and breakage including the role of ancient polyploidy. Abstract : A decade ago the concept of the Ancestral Crucifer Karyotype (ACK) and the definition of 24 conserved genomic blocks was presented. Subsequently, 35 cytogenetic reconstructions and/or draft genome sequences of crucifer species (members of the Brassicaceae family) have been analyzed in the context of this system; placing crucifers at the forefront of plant phylogenomics. In this review, we highlight how the ACK and genomic blocks have facilitated and guided genomic analysis of crucifers in the last 10 years and provide an update of this robust model.